1998
DOI: 10.1136/adc.78.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in Australia, 1993-95

Abstract: Aim-To describe the epidemiology, management, and rate of cardiac sequelae of Kawasaki disease in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
72
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 25 publications
10
72
0
2
Order By: Relevance
“…18 A previous Australian KD epidemiology study reported 2 Aboriginal children of a total of 139 KD patients identified by enhanced surveillance. 9 The overall rate of CA involvement was relatively high (23.4%), partly reflecting the pre-IVIG era during the first decade of study. 1 Boys were more likely to have CA involvement, a finding reported in other populations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…18 A previous Australian KD epidemiology study reported 2 Aboriginal children of a total of 139 KD patients identified by enhanced surveillance. 9 The overall rate of CA involvement was relatively high (23.4%), partly reflecting the pre-IVIG era during the first decade of study. 1 Boys were more likely to have CA involvement, a finding reported in other populations.…”
Section: Discussionmentioning
confidence: 94%
“…The current incidence of KD is almost threefold higher than the previously reported incidence, which was derived from enhanced national surveillance almost 20 years ago. 9 Extrapolating these findings to the Australian population suggests there are approximately 170 to 180 KD cases admitted nationally each year. The number of KD cases that are not diagnosed is unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Australia had annual incidences of 3.7 per 100 000 from 1993 to 1995, and Sweden had 6.2 from 1990 to 1992. 11,12 Why the incidence rates vary among countries remains unclear, but the difference possibly is related to a combination of factors, including race/ethnicity, environmental factors, and possible circulating infectious pathogens.…”
mentioning
confidence: 99%
“…По международным данным, заболеваемость колеб-лется в пределах 3,4-100 на 100 тыс. [7,9,11,13]. Болезни наиболее подвержены дети до 5 лет с пиком заболеваемости в возрасте 9-11 мес.…”
Section: семинар памяти профессора на белоконьunclassified